Effect of processing on the in vitro digestion characteristics of oat products by using a dynamic rat stomach-duodenum model. (October 2019) - Feng, Yuan; Wang, Xiaolong; Ma, Zhen; Ren, Tian; Li, Xiaoping; Hu, Xinzhong
Graphical abstract: Highlights: Processing increased the digesta viscosity decline rate of oat products. Processing increased gastric emptying and glucose concentration of oat products. Oatmeal (OM) and oat wowo (OW) belonged to low GI food. Processing leaded to a coarse starch structure of oat products. Abstract: This study investigated the in vitro digestive behavior of different processed oat products using a dynamic rat stomach and duodenum model. The changes in gastric emptying with respect to digestion time, glucose concentration, estimated glycemic index (GI), rheological and microstructural properties of the gastric and duodenal digests were determined. The results showed that the digesta viscosity of oatmeal (OM), oat wowo (OW), oat paste (OP) and oat rice (OR) decreased faster than unprocessed oat (UO) during digestion. Glucose concentration and gastric emptying increased with decreasing viscosity of oat products digesta at each digestion time. OR and OP had a higher gastric emptying rates and glucose concentration as compared to UO, OM and OW. The estimated GI of UO, OM and OW were lower than 55 and belonged to low GI food. The porous structures of oat products observed indicated that thermal treatments can change the digestion characteristics of oat products.